Pemantauan Pelaksanaan Asesmen Nasional Berbasis Komputer (ANBK) Sekolah Dasar Binaan Kecamatan Kopang Kabupaten Lombok Tengah Tahun 2021 - Ahmad, Ahmad (Jurnal Paedagogy, 2022)
The purpose of this study is to describe the monitoring of the Implementation of the Computer-Based National Assessment (ANBK) at the Kopang District Primary Schools in 2021. The research method used is a descriptive method. The research data collection techniques used were observation, interviews, and documentation. While the data analysis technique used descriptive qualitative and quantitative analysis. The results of the study indicate that in order to improve the quality and quantity of the implementation of ANBK in the future, it is necessary to: (1) Improve the competence of educators and education staff in preparing literacy and numeracy-oriented questions in each subject through workshops. (2) Capacity building of educators and education staff in implementing school digitization through IHT. (3) Increasing the provision of ANBK facilities and infrastructure by procuring at least one IT laboratory space in one school cluster through DAK. (4) Increasing the availability of computer/laptop equipment through the use of Regular/Affirmative/Performance BOS funds. (5) Capacity building of school principals in school management. (6) Increasing the capacity of school supervisors in academic supervision and managerial supervision. (7) Empowerment of KKG, KKKS and KKPS forums in completing their respective main tasks and functions.